2009
DOI: 10.1080/01612840902807947
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy: The Struggles in the Decision-Making Process and the Aftermath of Treatment

Abstract: The perceptions of patients and their family members about electroconvulsive therapy (ECT) are crucial to understanding the meaning attached to having ECT and the impact it has on quality of life. Thus, in this qualitative study, patients and their family members described their perceptions of having electroconvulsive therapy (ECT). The experience occurred in two distinct periods in the patient's life: making the decision to have ECT and the physical and emotional aftermath of treatment. One of the most import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…That study, conducted by Rajkumar, Saravana, and Jacob in 2007, revealed perceptions of coercion to give consent for ECT. The findings of Smith et al (2009) and van Daalen-Smith (this issue) concurred. Patients and family members reported feeling fearful, powerless, vulnerable, and desperate at the moment of decision-making.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…That study, conducted by Rajkumar, Saravana, and Jacob in 2007, revealed perceptions of coercion to give consent for ECT. The findings of Smith et al (2009) and van Daalen-Smith (this issue) concurred. Patients and family members reported feeling fearful, powerless, vulnerable, and desperate at the moment of decision-making.…”
supporting
confidence: 76%
“…ECT has been proven effective. What the papers by Smith et al (2009) and van Daalen-Smith (this issue) remind us is that nurses must be concerned with more than the scientific evidence that a treatment is effective. Melnyk (2011) is adamant that patient preferences and values must be considered, not only the scientific evidence about outcomes.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…When survivor testimony has been included in nursing journals, it paints a troubling picture. In a phenomenological study that asked patients to describe in their own words how ECT impacted the quality of their life, Smith et al (2009) found that the decision to have electroshock was the product of severe mental anguish, the belief that ECT was a last resort, and blind trust in their doctor. After receiving electroshock, the study participants experienced side effects that were more severe than they had been led to expect.…”
Section: Gaps In the Nursing Literaturementioning
confidence: 99%
“…Smith et al (2009) has led the way and opened the door for further phenomenological research in nursing regarding the lived experience of those receiving electroshock. Further, a more balanced representation of electroshock's controversial nature, impact, and outcome is crucial if nursing and nurses are to be the patient advocates we are called to be.…”
Section: Conclusion: a Gap Existsmentioning
confidence: 98%